Peran supervisi kepala sekolah dalam meningkatkan kinerja guru dalam pelaksanaan pembelajaran pada SMK Negeri 1 Klego Kabupaten Boyolali - Suprihono, Suprihono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the supervisory role of the principal in improving teacher performance in implementing learning at SMK Negeri 1 Klego, Boyolali Regency. This study uses a school action research design (PTS) designed in two cycles, namely, cycle I and cycle II. The subjects of this study were teachers at SMK Negeri 1 Klego. Data analysis uses qualitative data analysis which originates from primary and empirical data. The results showed that the supervision of the school principal played a role in improving teacher performance in implementing learning at SMK Negeri 1 Klego Boyolali Regency where overall teacher performance was already in good performance (100%) because it had a percentage of performance that was above (Above 76%)